Deformable, resilient, and mechanically-durable triboelectric nanogenerator based on recycled coffee waste for wearable power and self-powered smart sensors. (January 2021) - Li, Mengjiao; Cheng, Wei-Yuan; Li, Yi-Chiun; Wu, Hsing-Mei; Wu, Yan-Cheng; Lu, Hong-Wei; Cheng, Shueh-Lian; Li, Lei; Chang, Kuan-Chang; Liu, Heng-Jui; Lin, Yen-Fu; Lin, Lu-Yin; et al.
Abstract: Maximizing resource recycling and finding renewable energy sources are important for a sustainable environment considering the development and consumption of electronic products with the advancement of the internet of things and artificial intelligence technologies. Herein, an economic and environment-friendly triboelectric nanogenerator derived from the discarded coffee ground waste (CG-TENG) is developed to serve as a light-weight and shape-adaptive energy source and self-powered sensitive sensor (CG-TENG sensor). The coffee ground, embedded into the silicone rubber elastomer, is first used as the metal-free electrode feedstock to minimize waste generation. Based on the triboelectrification and electrostatic induction, the shape-adaptive CG-TENG, as wearable power, is capable of harvesting surrounding energy from human motions and extreme deformations, exhibiting excellent stretchability and mechanical durability. The generated electricity can be stored in the conductive coffee ground-derived capacitors to drive portable electronics, which is beneficial for building completely green power systems using coffee waste. Furthermore, the self-powered CG-TENG sensor with optimized structure endows its ultra-high sensitivity for sensing human physiological signals, monitoring motions, emulating gestures, as well as for developing smart tactile epidermal controller and intelligent vending coaster, paving the way for building large-scale energy-efficient artificial sensors and eco-environmental wearable electronics towards humanoid robotics and human-machine interfaces. Graphical abstract: This coffee ground-derived TENG with advantages such as low-cost, environmental friendliness, as well as excellent stretchability, deformability, and durability, is effective both in mechanical energy harvesting and self-sufficient pressure sensing including motion monitoring, emulation, and acting as smart human-machine interface. These results provide a promising paradigm for developing eco-environmental wearable equipment and intelligent user interface systems. Image 1 Highlights: The typical biomass of coffee ground is employed as the conducting electrode, for the first time, to develop metal-free and environmental-friendly TENG. The coffee ground-based TENG enables to harvest various mechanical energy under extreme deformations, demonstrating its outstanding advantages in high stretchability, durability, and environmental friendliness. The harvested energy can be stored in a coffee ground-based supercapacitor to drive portable electronic devices, indicating its promising uses in low-cost wearable power sources. Such the coffee waste-derived TENG e-skin sensor sensitively perform the real-time physiological signals detection, motion monitoring/emulation, as well as sensitive human-interactive functions, providing a new vista for the development of economic and environmentally friendly wearable electronics.